Blue Monday - French, Nicci, ....- (London : Joseph, 2011)
Frieda Klein is a solitary, incisive psychotherapist who spends her sleepless nights walking along the ancient rivers that have been forced underground in modern London. She believes that the world is a messy, uncontrollable place, but what we can control is what is inside our heads. This attitude is reflected in her own life, which is an austere one of refuge, personal integrity, and order. The abduction of five-year-old Matthew Farraday provokes a national outcry and a desperate police hunt. And when his face is splashed over the newspapers, Frieda cannot ignore the coincidence: one of her patients has been having dreams in which he has a hunger for a child. A red-haired child he can describe in perfect detail, a child the spitting image of Matthew. She finds herself in the center of the investigation, serving as the reluctant sidekick of the chief inspector. Drawing readers into a haunting world in which the terrors of the mind have spilled over into real life, Blue Monday introduces a compelling protagonist and a chilling mystery that will appeal to readers of dark crime fiction and fans of In Treatment and The Killing.
Keywords: Fiction